A Simplified Process for High Purity of N-[1-(s)-Ethoxycarbonyl- 3-phenylpropyl]-(s)-alanine-N-carboxyanhydride - V. Sureshbabu, Chillara; Parihar, J.A.; Muralikrishna, D. (Asian Journal of Chemistry, 2010)
N-[1-(s)-Ethoxycarbonyl-3-phenylpropyl]-(s)-alanine-Ncarboxyanhydride is prepared in very high purity by intramolecular cyclization of carbamate (I) using N,N-dimethyl aniline as base and without any tedious purification.